2021
DOI: 10.1001/jamainternmed.2020.9285
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Multifaceted Clinical Pharmacist Intervention on Medication Safety After Hospitalization in Persons Prescribed High-risk Medications

Abstract: Event (ADE) Prevention identified 3 high-priority, high-risk drug classes as targets for reducing the risk of drug-related injuries: anticoagulants, diabetes agents, and opioids.OBJECTIVE To determine whether a multifaceted clinical pharmacist intervention improves medication safety for patients who are discharged from the hospital and prescribed medications within 1 or more of these high-risk drug classes. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial was conducted at a large multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…These results are also well supported by the studies of Wang et al and Rodriguez et al [ 42 , 53 ]. Review findings reported pharmacists regularly monitored the records of patients admitted to ICUs, reviewed their prescriptions and lab reports, managed their medication errors and did interventions to balance their electrolytes and these findings were supported by the literature [ 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 83%
“…These results are also well supported by the studies of Wang et al and Rodriguez et al [ 42 , 53 ]. Review findings reported pharmacists regularly monitored the records of patients admitted to ICUs, reviewed their prescriptions and lab reports, managed their medication errors and did interventions to balance their electrolytes and these findings were supported by the literature [ 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 83%
“…Eleven of the included studies were individually randomised [ 24–34 ], and eight studies were cluster-randomised [ 35–42 ]. Eight of the studies were conducted in the United States [ 24 , 28–30 , 33 , 35 , 38 , 40 ], eight in Europe [ 25–27 , 31 , 37 , 41 , 42 ] and two in Australia [ 36 , 39 ] and one in New Zealand [ 32 ]. The sample size ranged from 81 to 3,904 participants, and the mean age between 67 and 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…Patients scheduled for readmission were less likely to be unscheduled readmission, which may have resulted in a lower rate of unscheduled readmissions in the no suggestions group. Cochrane review suggested that it is uncertain whether interventions for polypharmacy and medication reviews reduces hospital admissions, quality of life, or mortality [ 9 , 27 ], and subsequent randomized clinical trial also did not demonstrate that clinical pharmacist intervention can reduce adverse drug-related incidents or clinically important medication errors during the posthospitalization [ 28 ]. Whereas, the other randomized clinical trial suggested that clinical pharmacist intervention including follow-up after discharge can reduce the number of emergency department visits and hospital readmissions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%